Nursing Management of Medication Errors - Luk, Leung Andrew (Nursing ethics, 2008)
Medication error is the most common and consistent type of error occurring in hospitals. This article attempts to explore the ethical issues relating to the nursing management of medication errors in clinical areas in Macau, China. A qualitative approach was adopted. Seven registered nurses who were involved in medication errors were recruited for in-depth interviews. The interviews were transcribed and analyzed using content analysis. Regarding the management of patients, the nurses acknowledged the mistakes but did not disclose the incidents to patients and relatives. Concerning management of the nurses involved by senior staff, most participants experienced fairness, comfort and understanding during the process of reporting and investigation. The ethical issues relating to the incidents were discussed, particularly in the Chinese context. There is a need for further study relating to the disclosure of medication incidents to patients and some suggestions were made.